Incidental Findings on Foot and Ankle Radiographs as Compared to Other Anatomic Regions. Issue 4 (16th October 2019) - Velasco, Brian; Ye, Michael; Chien, Bonnie; Kwon, John Y.; Miller, Christopher P.
Category: Orthopedic Radiology Introduction/Purpose: Radiographs are one of the most common and widely available diagnostic imaging techniques that are used to evaluate orthopedic conditions. However, incidental findings on imaging may be observed as well, some of which may be very serious and have significant heath as well as legal ramifications if missed. This study evaluates the number of clinically relevant incidental findings reported for orthopaedic radiographs ordered in an academic orthopedic multispecialty group over one year. Methods: A retrospective review was conducted of 13, 948 eligible radiographs recorded at our institution over a 12-month period. Reports were categorized based on exam type. Incidental findings were first categorized as either concern for malignancy or non-malignancy. The possibly malignant findings were further subdivided into malignancies in Bone or Lung tissues. The non- malignant findings were categorized into the following groups: Benign Bone Disease, Gastrointestinal Pathology, Gynecologic Pathology, Incidental Fracture, Infection, Inflammation, Respiratory Pathology, Soft Tissue Mass, Urologic Pathology, Vascular Pathology or Other. Results: Of the 13, 948 radiographs, 286 radiographs reported at least one incidental finding totaling to 287 (2.06%) incidental findings. The 3 studies with the highest rates of incidental findings were Leg Length Alignment films (3.94%), Spine (3.88%), and Pelvis & Hip (2.76%). The three categories with the lowest rates of incidental findings were Hand & Wrist (0.56%), Tibia/Fibula Foot & Ankle (0.84%), and Forearm & Elbow (1.13%). Over one-third of incidental findings concerned malignancy or metastases with 87 (30.1%) and 18 (6.23%) identified in bone tissue and lung tissue, respectively. Benign Bone Disease (24.9%), Gastrointestinal Pathology (6.57%), and Gynecologic Pathology (5.88%) were categories with the highest rates of non-malignant incidental findings. Follow-up was recommended for 122 (42.5%) incidental findings. Conclusion: This study describes the rates of incidental findings on orthopedic radiographs. Radiographs of midline structures are more likely to report an incidental finding as opposed to radiographs of distal extremities. The exception is leg alignment films because these image the entirety of the lower extremity and the pelvis and thus a far larger volume of the body. Over one-third of incidental findings concerned possible malignancy or metastases and therefore follow-up with focused imaging should be recommended if suspicious. This information will be particularly useful for orthopaedic surgeons who read their own radiographs without a radiologist formally reviewing the films.